Regulation Of Zakah: An Analytical Study In The Light Of Maqasid Shariah - Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi; Azman Ab. Rahman (Intelligentia Resources, 2024)
The shari'a of Islam's distinctive specification is based on the law's flexibility in question. History has proven that many fiqh issues vary in their laws, considering various primary factors of current and local values. It takes credit for its philosophy of adapting the law to achieve maqasid shari'ah, which is to make provision for the people's welfare – known as taḥqīq maṣāliḥ al-ʿibād-, maintaining this noble intention and safeguarding it from any damage. In the context of Maqasid Shariah, this paper aims to examine the regulation of zakat critically. A qualitative methodology was employed to analyse the data through inductive, deductive, comparative. The findings show that the safeguarding act centralises on the essential (al-ḍaruriyyāt), the complimentary (al-ḥājiyyāt) and the embellishments (al-taḥsiniyyāt), and maintains these five tenets (ḍaruriyyāt al-khams) namely; prevention of religion (ḥifẓu ad-dīn), prevention of life (ḥifẓu an-nafs), prevention of intellect (ḥifẓu al-ʿaql), prevention of progeny (ḥifẓu an-nasb), and prevention of property (hifzu al-mal). In the context of zakat, it has stood in prominence in safeguarding the maslahah asnaf and the Muslim economy (ḥifẓu al-māl), particularly in Malaysia. It is proposed that Zakat Corporations and Islamic Religious Councils of every State in Malaysia should frequently reassess the existing ruling and legal framework of zakat in order to harmonise with the objective of zakat.